Implementasi Strategi Pemasaran Usaha Jasa Pembuatan Furnitur Pada Mebel Tiga Putra Selatan - Rindy Rahmawaty; Semuel Batlajery; Fenty Manuhutu (Musamus Journal of Business & Management, 2022)
The purpose of this study was to determine the application of marketing implementation in the service business sector in the manufacture of furniture at the Tiga Putra Selatan Furniture which is located on the Street of Seringgu Jaya. To obtain research data, researchers interviewed 10 informants. In this study, non-probability sampling method is used, which means that the sampling technique is not chosen at random, then snowball sampling is used, which is taking samples that are initially small in number and then develop into larger ones. This study uses a qualitative method with a descriptive approach, while the data analysis technique uses three stages: Data Reduction (Data Reduction), Data Display (Data Display), Verification (Conclusion Drawing). Based on the results of the research conducted, using SWOT analysis, as well as internal and external analysis, the IE matrix and the SWOT matrix, the results showed that Tiga Putra Selatan Furniture was in quadrant 1 (Aggressive). The strategy that can be used is the SO strategy, which is to increase the strengths possessed by taking advantage of existing opportunities to minimize weaknesses and prevent future threats.